Prevalence of periodontal disease, oral mucosal lesions and oral habits among seafood industry employees of Visakhapatnam, Andhra Pradesh - Anakapalli Sai Praharsh; L. V. K. Reddy; Pydi Sivakumar; Pottem Nagarjuna; Rachuru Yashwanth Sai; Polapala Sugeethika (The Saint's International Dental Journal, 2024)
Background: Epidemiological studies serve to generate knowledge of the distribution and determinants of disease frequency. To be able to find effective tools for prevention and health promotion, we have to know the causation that preceded the disease onset. Aim: To assess the periodontal status, prevalence of oral mucosal lesions, and oral habits among seafood industry employees in Visakhapatnam district, Andhra Pradesh. Materials and Methods: A cross-sectional survey was conducted among 162 participants aged between 18 and 60 years of age, using WHO oral health questionnaire for adults (2013) and the oral health assessment form for adults (2013), which recorded demographic details, routine oral hygiene habits, adverse oral habits, community periodontal index, and oral mucosal lesions. Descriptive statistics were performed to analyze frequency and percentage distribution of study variables. Results: The majority of the subjects used a toothbrush (98.1%) and toothpaste (97.5%) to clean their teeth. Smoking and tobacco chewing habits were recorded among 41 (25.3%) and 21 (12.9%) subjects, respectively. The prevalence of periodontal disease was 79.6% among the study population. About four (2.4%) subjects had leukoplakia, five (3.1%) subjects had ulcerations, and three (1.8%) subjects had smoker’s palate. Conclusion: The findings of this study provided an insight into the periodontal health status, oral habits, and the prevalence of oral mucosal lesions of seafood industry employees in Visakhapatnam, which may be useful in designing and planning oral health promotion programs.